Doing fieldwork the Chinese way: a returning researcher's insider/outsider status in her home town. Issue 2 (21st March 2017) - Zhao, Yawei
Abstract : Insider/outsider status has been recognised in geographical literature as an important aspect of positionality on which researchers should reflect critically. Based on my fieldwork experience in Dali, southwest China, this paper articulates an account of the co‐existence of 'insiderness' and 'outsiderness' during the research process in a way that adds nuance to scholarly challenges to conceptions of insider/outsider status as an oppositional binary. I touch on several dilemmas that arose over the course of my fieldwork in my home town, such as working with local research assistants, 'encountering' a Western supervisor in the field and interviewing local people. I argue that interacting in the field with people from different ethnic, professional or socioeconomic characteristics dynamises a researcher's insider/outsider position, bringing his or her in‐between position to the fore. In this paper, I highlight the tensions and negotiations arising from my experience of in‐betweenness in Dali. I also point out several particularities of doing fieldwork in China by referring to Chinese ways of thinking and communication, and analyse how insiderness complicates the research process with particular regard to China. Finally, I conclude that working in the field is not only a process of data collection, but also a process of learning 'who I am'.